Dealing with applications in Industrial IoT - Radhika Sreedharan (Universitas Respati Yogyakarta, 2023)
Industrial Internet of Things (IIoT) also known as Industry 4.0, consists of industries that utilize IoTs to facilitate logistics, manufacturing, transportation, oil and gas, energy/utilities, mining and metals, aviation, and others. Though a lot of companies have proceeded into a lot of areas utilizing IIoT, its applicability in a lot of is still not explored and remains unpredictable. Its evolution is similar to that of the Internet in the early 90s, where it initially appeared and slowly gained momentum in the 20th century to almost becoming and indispensable aspect of human life in the 21st century. Robotics and control are already a part of most of the manufacturing companies, however, when it comes to real-time applications in manufacturing, IIoT may not come to the rescue. Another aspect that separates the internet and IIoT is that the internet is based on the bet effort delivery model which is acceptable for e-commerce and man-machine interactions. However, failures in an IIoT scenario such as air-traffic monitoring, automated manufacturing can have serious consequences. Industry 4.0 is an initiative taken up by industries to use IoT in industries and many such initiatives have been taken up by different companies and countries. For example, GE has already invested 1billion to improve its asset performance and business operation by using IIoT services. Germany has started an initiative called “Industry 4.0”, a strategic initiative that brought together leaders from private and public sectors as well as from academia to create a detailed plan of action for incorporating digital technologies into German industries. Other countries such as Italy, Netherlands, and France have invested in setting up smart factories and industries. China has also started a project called “Made in China 2025” to integrate digital technologies and industrialization. A major hindrance in adopting IIoT is that the smart devices often speak different “languages” that existing industrial automation software uses, which creates a communication gap, and hence standardization is necessary. Overcoming such bottlenecks and adopting IIoT can help automate the production techniques, for instance, manufacturers could increase their productivity by a margin of 30%. The capabilities of IIoT can be explored in areas such as sensor-driven computing, industrial analytics, and intelligent machine applications. The main aim of this topic is to explain various applications inf IoT in industries